2019
DOI: 10.1016/j.kint.2018.08.037
|View full text |Cite
|
Sign up to set email alerts
|

The proteome microenvironment determines the protective effect of preconditioning in cisplatin-induced acute kidney injury

Abstract: The protective effect of preconditioning in cisplatin-induced acute kidney injury is determined by mRNA-independent alterations of the proteome microenvironment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 70 publications
(77 reference statements)
2
55
0
Order By: Relevance
“…These differences may be due to differences between the species, but additionally, the renal changes associated with the allogeneic rat transplantation model resemble chronic rejection [25] and thus may reflect more immune-driven processes than the present biopsies from stable renal transplant patients. Moreover, a study by Späth et al confirmed our findings on the involvement of proteins related to inflammatory and fibrotic responses in kidney function and fibrosis [26].…”
Section: Discussionsupporting
confidence: 88%
“…These differences may be due to differences between the species, but additionally, the renal changes associated with the allogeneic rat transplantation model resemble chronic rejection [25] and thus may reflect more immune-driven processes than the present biopsies from stable renal transplant patients. Moreover, a study by Späth et al confirmed our findings on the involvement of proteins related to inflammatory and fibrotic responses in kidney function and fibrosis [26].…”
Section: Discussionsupporting
confidence: 88%
“…and various recent studies suggested that this effect is evolutionary conserved in a wide variety of species from yeast to mammals including primates. 34 With the likely cause responsible for this phenomenon being a robust and longstanding enhancement of cellular stress resistance 35,36 a short-term protection from acute stressors is achieved by brief periods of DR. With respect to the kidney, Mitchell et al published a proof-of-concept study in a murine renal ischemia reperfusion injury model in which DR conducted for 2 to 4 weeks completely prevented death from AKI and dramatically ameliorated renal failure. 3 Likewise, we showed recently that a 4-week 30%-CR strongly protects from toxic renal failure after cisplatinum application in mice.…”
Section: Discussionmentioning
confidence: 99%
“…3 Likewise, we showed recently that a 4-week 30%-CR strongly protects from toxic renal failure after cisplatinum application in mice. 35 Despite a plethora of studies investigating dietary interventions with respect to weight control, only scarce data is available concerning the impact of DR protocols on organ protection in humans. In a large-scale clinical trial the administration of a calorie-restricted enteral feeding protocol in critically ill patients led to a significantly lower rate of renal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…17 Notably, the recovery rates from AKI have not improved significantly over the last 60 years, 18 indicating a small increase in knowledge about the underlying pathogenetic processes. This is remarkable, given the numerous experimental studies dealing with the prevention and treatment of AKI (eg, 4,[19][20][21][22][23][24][25][26][27] ).…”
mentioning
confidence: 99%